2016
DOI: 10.3390/ijerph13100960
|View full text |Cite
|
Sign up to set email alerts
|

Activity Pattern of Urban Adult Students in an Eastern Mediterranean Society

Abstract: Knowledge of human activity patterns is needed in air pollution exposure and health risk assessment. However, human activity patterns have never been evaluated in the Eastern Mediterranean societies. Therefore, we investigated the activity pattern of 285 subjects (17–63 years) in Amman, Jordan during October to November, 2015. The subjects spent >80% of their time indoors during weekend days and >85% on workdays. They spent ~4.8% and ~5.7% in transportation during weekend days and workdays, respectively. Males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 17 publications
(32 reference statements)
2
11
1
Order By: Relevance
“…Time spent indoors was significantly higher than time spent outdoors in our study. Our youth displayed similar high percentages of time in buildings (89.58%) compared with the previous 90% values reported in other studies which included sleep time [ 9 , 36 ]. Our youth spent about 15 hours/day on indoor activities.…”
Section: Discussionsupporting
confidence: 89%
“…Time spent indoors was significantly higher than time spent outdoors in our study. Our youth displayed similar high percentages of time in buildings (89.58%) compared with the previous 90% values reported in other studies which included sleep time [ 9 , 36 ]. Our youth spent about 15 hours/day on indoor activities.…”
Section: Discussionsupporting
confidence: 89%
“…Study participants spent an average of 870 min per day at home, which is higher than at any other location. This is slightly lower than reported by other investigators, for example, Odeh and Hussein (2016) found that, on average, adult students in Jordan spent about 900 min at home (63%). Importantly, our finding of time spent at home is 70 min less than the 940 min reported by the U.S. National Human Activity Pattern Survey (NHAPS) as the average time spent by Americans indoors at home (Leech et al, 2002); 80 min less than the 950 min reported by the Canadian Human Activity Pattern Survey (CHAPS) that Canadians spend at home (Leech et al, 2002); and the average 940 min that Germans spend at home (Brasche and Bischof, 2005).…”
Section: Study Participants and Time Activity Patternscontrasting
confidence: 62%
“…Indoor air pollution has a significant impact on human respiratory and cardiovascular health because people spend the majority of their time in indoor environments, including their homes, offices, and schools [1][2][3][4][5][6][7][8][9]. The World Health Organization (WHO) has recognized healthy indoor air as a fundamental human right [4].…”
Section: Introductionmentioning
confidence: 99%